2019
DOI: 10.2116/analsci.19sap03
|View full text |Cite
|
Sign up to set email alerts
|

Ga Ion-doped ZrO2 Catalyst Characterized by XRD, XAFS, and 2-Butanol Decomposition

Abstract: and Tl; 5 mol%) were prepared by impregnation of each metal salt aqueous solution on amorphous zirconium hydroxide, followed by calcination at 773 K. The M-ZrO2 samples were characterized by the catalytic performance of 2-butanol decomposition at 573 K, XRD, XANES and EXAFS spectroscopic techniques. Detailed analyses were performed herein for a series of Ga-ZrO2 with various doping amounts in the range of 1-60 mol%. The addition of Group 2 and 3 elements little influenced the catalytic performance of ZrO2 itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In order to further investigate the local electronic structure of different catalysts, X‐ray absorption spectroscopy (XAS) analysis was conducted (Figures S13 and S14, Supporting Information). [ 53 ] According to the X‐ray absorption near‐edge structure (XANES) spectrum presented in Figure 2c, the lowest intensity Pt L III ‐edge white lines in the Pt 3 Ga (Pm 3¯$\bar{3}$ m) sample indicated that Pt atoms were less oxidized than those in the Pt foil, Pt 3 Ga (P4/mbm) and PtGa alloy. The formation of Pt‐Ga bonds could make absorption edges Pt shifted to higher energy, which meant that the increase of 5d orbital filling relative to Pt foil, explaining the change of XANES spectrum of PtGa samples.…”
Section: Resultsmentioning
confidence: 99%
“…In order to further investigate the local electronic structure of different catalysts, X‐ray absorption spectroscopy (XAS) analysis was conducted (Figures S13 and S14, Supporting Information). [ 53 ] According to the X‐ray absorption near‐edge structure (XANES) spectrum presented in Figure 2c, the lowest intensity Pt L III ‐edge white lines in the Pt 3 Ga (Pm 3¯$\bar{3}$ m) sample indicated that Pt atoms were less oxidized than those in the Pt foil, Pt 3 Ga (P4/mbm) and PtGa alloy. The formation of Pt‐Ga bonds could make absorption edges Pt shifted to higher energy, which meant that the increase of 5d orbital filling relative to Pt foil, explaining the change of XANES spectrum of PtGa samples.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, no discernible change in lattice spacing was observed when “a” exceeded 0.15, which suggests that there is a limit to the extent of Cu doping (approximately a=0.15). Ga–doped ZrO 2 , [28] Mn–doped ZrO 2 , [29] Zn–doped ZrO 2 , [8b] and Mn–doped CeO 2 [30] have been similarly analyzed.…”
Section: Characterizing Oxide Solid Solutionsmentioning
confidence: 99%
“…Recent studies show that Ga 2 O 3 works as a stabilizer for high-temperature phases of zirconia, [32,33] with 3 mol% of Ga 2 O 3 permitting full stabilization of the cubic/tetragonal high-temperature phases. Yamamoto et al also did not distinguish between the cubic and tetragonal phase due to the overlapping of the peaks in XRD analyses of these two phases.…”
Section: Phase Transformation Of Zromentioning
confidence: 99%